A Semi‐Synthetic Glycoconjugate Vaccine Candidate for Carbapenem‐Resistant Klebsiella pneumoniae. (5th October 2017) - Seeberger, Peter H.; Pereira, Claney L.; Khan, Naeem; Xiao, Guozhi; Diago‐Navarro, Elizabeth; Reppe, Katrin; Opitz, Bastian; Fries, Bettina C.; Witzenrath, Martin
Abstract: Hospital‐acquired infections are an increasingly serious health concern. Infections caused by carpabenem‐resistant Klebsiella pneumoniae (CR‐ Kp ) are especially problematic, with a 50 % average survival rate. CR‐ Kp are isolated from patients with ever greater frequency, 7 % within the EU but 62 % in Greece. At a time when antibiotics are becoming less effective, no vaccines to protect from this severe bacterial infection exist. Herein, we describe the convergent [3+3] synthesis of the hexasaccharide repeating unit from its capsular polysaccharide and related sequences. Immunization with the synthetic hexasaccharide1 glycoconjugate resulted in high titers of cross‐reactive antibodies against CR‐ Kp CPS in mice and rabbits. Whole‐cell ELISA was used to establish the surface staining of CR‐ Kp strains. The antibodies raised were found to promote phagocytosis. Thus, this semi‐synthetic glycoconjugate is a lead for the development of a vaccine against a rapidly progressing, deadly bacterium.